Stress hyperglycemia ratio and the clinical outcome of patients with heart failure: a meta-analysis - Li, Liang; Zhao, Zhikun; Wang, Shasha; Wang, Jiajia (Frontiers in Endocrinology, 2024)
Background: Stress hyperglycemia ratio (SHR) is a newly suggested measure of stress-induced hyperglycemia that combines both short-term and long-term glycemic conditions. The study aimed to explore the association between SHR and the incidence of adverse clinical events with heart failure (HF) through a meta-analysis.Methods: Cohort studies relevant to the aim of the meta-analysis were retrieved by search of electronic databases including PubMed, Web of Science, Embase, Wanfang, and CNKI. A random-effects model was used to combine the data by incorporating the influence of between-study heterogeneity.Results: Ten studies involving 15250 patients with HF were included. Pooled results showed that compared to patients with lower SHR at baseline, those with a higher SHR were associated with an increased risk of all-cause mortality during follow-up (risk ratio [RR]: 1.61, 95% confidence interval [CI]: 1.17 to 2.21, p = 0.003; I 2 = 82%). Further meta-regression analysis suggests that different in the cutoff of SHR significantly modify the results (coefficient = 1.22, p = 0.02), and the subgroup analysis suggested a more remarkable association between SHR and all-cause mortality in studies with cutoff of SHR ≥ 1.05 than those with cutoff of SHR < 1.05 (RR: 2.29 versus 1.08, p for subgroup difference < 0.001). Subsequent meta-analyses also showed that a high SHR at baseline was related to the incidence of cardiovascular death (RR: 2.19, 95% CI: 1.55 to 3.09, p < 0.001; I 2 = 0%), HF-rehospitalization (RR:1.83, 95% CI: 1.44 to 2.33, p < 0.001; I 2 = 0%), and major adverse cardiovascular events (RR: 1.54, 95% CI: 1.15 to 2.06, p = 0.004; I 2 = 74%) during follow-up. 3 Conclusion: A high SHR at baseline is associated with a poor clinical prognosis of patients with HF.